Students’ perceptions toward the implementation of case method learning in Listening Class at Universitas Negeri Padang - Ningsih, Sucita Rahma; Ayudhia, Honesty Yonanda (Universitas Negeri Padang, 2025)
This research examined students' perceptions toward the implementation of case method learning in Advanced Listening classes at Universitas Negeri Padang. The case method, a discussion-based participatory learning approach, was applied to address challenges students faced in listening comprehension, including limited vocabulary, concentration difficulties, and linguistic problems. This descriptive quantitative study involved 70 students from three Advanced Listening classes in the 2023 academic year, selected through cluster random sampling. Data were collected using a validated and reliable questionnaire consisting of 25 statements measured on a four-point Likert scale, covering five indicators: Learning Process Effectiveness, Critical Thinking Development, Active Participation and Engagement, Skill Development, and Learning Environment. The findings revealed that students held positive perceptions across all indicators, with an overall mean score of 3.08. Learning Process Effectiveness achieved the highest mean score of 3.18, followed by Learning Environment (3.13), Active Participation and Engagement (3.06), Critical Thinking Development (3.04), and Skill Development (3.00). These results indicate that the case method effectively facilitates listening comprehension, fosters a supportive learning atmosphere, promotes engagement, enhances critical thinking, and develops practical listening skills. Therefore, it can be concluded that the case method serves as an effective pedagogical approach that enriches students’ learning experiences and supports comprehensive learning outcomes in Advanced Listening instruction.